The Sosialisasi dan Pelatihan Pemanfaatan Sampah Organik Rumah Tangga Menggunakan Komposter di Gili Air - Siska Ita Selvia; Sukartono Sukartono; Lalu Arifin Aria Bakti; Suwardji Suwardji; Bambang Hari Kusumo (Institut Pertanian Bogor, 2024)
Gili Air is part of a group of small islands without waste problems. Efforts to reduce and manage waste in Gili Air, Gili Indah Village, still need to be improved, considering that the potential for waste generation is still significant, especially organic waste, which is 55% of the total potential for waste generation. The potential for recycling waste on Gili Air shows a waste-carrying capacity index value of 0.20, which means it is lower than the generation potential. It impacts Gili Air's relatively low level of waste support. As a tourist destination, Gili Air produces solid waste from local communities and tourism activities. This community service activity aims to increase awareness of the community and business owners in the tourism sector in Gili Air to reduce the rate of daily waste generation by reducing and utilizing organic waste to be processed into solid or liquid compost. The method applied for community service on Gili Air is in the form of outreach and training, demonstrating the stages of composting using a simple process that is easy for local communities to implement. Based on the results of monitoring and evaluation of community service activities, there was an increase in understanding of community service participants. It is indicated by a decrease in the percentage of wrong answers from the questionnaire announced after the service activity (post-test). In the pre-test before receiving community service, it was discovered that 59% of people still answered the statement on the questionnaire wrong. However, wrong answers decreased to only 12% after socialization and training. Increasing understanding of the pre-and post-test statements shows that socialization and training can positively impact community empowerment in managing household waste into solid and liquid fertilizer.